The effect of changing employers' access to criminal histories on ex-offenders' labor market outcomes: Evidence from the 2010-2012 Massachusetts CORI Reform - Osborne Jackson; Bo Zhao (Federal Reserve Bank of Boston, 2017)
Many regard the 2010-2012 Massachusetts Criminal Offender Record Information (CORI) Reform as a national model to improve ex-offenders' labor market outcomes. This reform prohibits most employers from inquiring about an individual's criminal history on the initial job application (the "ban the box" reform), and reduces employers' access to an applicant's criminal record (the record-access reform). Using the CORI Reform as a natural experiment and a unique large confidential dataset linking individuals' CORI records with their unemployment insurance quarterly wage records, we examine the impact of changing employers' access to applicants' criminal histories on ex-offenders' labor market outcomes. We find that contrary to the intended goal, the CORI Reform has a small negative effect on exoffenders' employment that grows over time, with mixed effects on earnings and industry composition. Suggestive evidence shows that the negative employment effect is more likely to result from a labor supply response rather than a labor demand response to the policy changes.
Keywords: K14; K40; K42; 330; ex-offenders; criminal history; Massachusetts CORI Reform; ban the box